2007
DOI: 10.1097/ftd.0b013e31811fef29
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality and Drug Concentrations in Seminal Plasma of Patients Using a Didanosine or Didanosine Plus Tenofovir Containing Antiretroviral Regimen

Abstract: Data on the concentrations of didanosine (ddI) and tenofovir (TFV) in seminal plasma are sparse. Subtherapeutic drug concentrations within the lumen of the male genital tract may have implications for selection and transmission of drug-resistant HIV strains. On the other hand, sufficient penetration of these drugs into the male genital tract has potential toxic effects on the spermatozoa and their precursors. In the current study, the authors obtained paired semen and blood samples at variable time points afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The discrepancy between the median C 24 values probably results from the steady-state condition and an accumulation of TFV in the male genital tract with repeated administrations. Other studies have reported higher TFV concentrations in SP, with SP-to-BP concentration ratios of 2.8 and 3.3 (13,14). The mean C 24 ratio at steady state was reported to be 5.1 (15), close to the mean C 24 ratio at steady state of 6.6 estimated in our study.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The discrepancy between the median C 24 values probably results from the steady-state condition and an accumulation of TFV in the male genital tract with repeated administrations. Other studies have reported higher TFV concentrations in SP, with SP-to-BP concentration ratios of 2.8 and 3.3 (13,14). The mean C 24 ratio at steady state was reported to be 5.1 (15), close to the mean C 24 ratio at steady state of 6.6 estimated in our study.…”
Section: Discussionsupporting
confidence: 75%
“…Available data on tenofovir (TFV) SP concentrations are sparse, although this drug is recommended as a preferred choice in first-line regimens for HIV treatment and postexposure prophylaxis and a large body of evidence from trials using TFV-based regimens now supports the concepts of "treatment as prevention" and "preexposure prophylaxis" (11,12). Four studies have suggested an accumulation of TFV in the male genital tract to different extents (13)(14)(15)(16). Mean TFV SP-to-BP concentrations ratios have been estimated at 2.8 (n Ï­ 4 men) and 3.3 (n Ï­ 15 men) for various sampling times (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data have shown seminal plasma concentrations of zidovudine (AZT, 39-azido-39-deoxythymidine) and didanosine (ddI, 29,39-dideoxyinosine) are up to 10-fold higher than blood plasma (Lowe et al, 2007;Dumond et al, 2008). Understanding the transepithelial transport pathway NRTIs use to bypass the BTB could potentially be useful in designing other drugs to cross into the lumen of seminiferous tubules.…”
Section: Introductionmentioning
confidence: 99%
“…The model developed for 3TC could be applied to FTC disposition in the male genital tract, if such data were available. The penetration of TDF into SP has been studied by several groups (25,26), but only one paper has examined its active diphosphate form in SMCs (27). Vourvahis and colleagues found 9-fold-higher concentrations of the diphosphate in SMCs at a first dose of TDF monotherapy, and 17-fold-higher concentrations in SMCs at steady state; in SMCs, these concentrations exceed the proposed IC 90 in PBMCs (16 fmol/10 6 cells) (28) by at least 10-fold.…”
Section: Discussionmentioning
confidence: 99%